Cutaneous Mucormycosis in a Diabetic Patient following Traditional Dressing - Zahra Ahmadinejad; Hamideh Khazraiyan; Fahime Ghanbari; Bahram Ahmadi; Mohsen Gerami Shoar (Case Reports in Dermatological Medicine)
Cutaneous mucormycosis is a rare manifestation of an aggressive fungal infection. Early diagnosis and treatment are vitally important in improving outcome. We report an unusual case presenting with progressive necrotizing fasciitis due to mucormycosis following trauma and dressing by man-made herbal agents.